Bilateral agreement for academic years 2011/2013 Lifelong Learning Programme: higher education - Erasmus between Universidade Lusíada de Lisboa and Universidad CEU San Pablo - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the LLP programme. - Subject area: Business studies; Communication; Publicity; Law.